Re-interpretation of Islamic Transaction Principles in Economic Activities - Johar, Johar; Maghfirah, Maghfirah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Muʻamalah, as a human activity related to devotion to Allah, must abide by the rules established by Islamic law for the benefit of society and the maintenance of rights and duties among people. Therefore, the purpose of this paper is to provide a comprehensive and applicable explanation of the reinterpretation of Islamic transactional principles in 21st century economic activities. This article is a library study using qualitative methods. Methods for collecting document data from relevant journals and books. It is then analyzed using content analysis methods. The result of this research is the principles of Islamic transactions: (1) mashlahah as an indicator of transactions, (2) justice in transactions, and (3) prohibition of all transactions involving ribâ, gharâr, tadlîs, tahkîr, maysîr, and risywah. The similarity between the study and previous studies lies in the concept and principles of Islamic transactions, but the difference is that this study fully explains the principles of Islamic transactions, with examples of their application in economic activities. Muʻamalah, sebagai aktivitas manusia yang berhubungan dengan pengabdian kepada Allah, harus mematuhi aturan yang ditetapkan oleh hukum Islam untuk kemaslahatan masyarakat dan pemeliharaan hak dan kewajiban di antara orang-orang. Oleh karena itu, tujuan dari makalah ini adalah untuk memberikan penjelasan yang komprehensif dan aplikatif tentang reinterpretasi prinsip-prinsip transaksional Islam dalam kegiatan ekonomi abad ke-21. Artikel ini merupakan studi literatur dengan menggunakan metode kualitatif. Metode pengumpulan data bibliografi dari jurnal dan buku yang relevan. Kemudian gunakan metode analisis isi untuk menganalisis. Hasil penelitian ini adalah prinsip-prinsip perdagangan Islam: (1) maslahah sebagai indikator perdagangan, (2) keadilan perdagangan, dan (3) larangan semua transaksi yang melibatkan ribâ, gharâr, tadlîs, tahkîr, maysîr dan risywah. Kesamaan dengan penelitian sebelumnya terletak pada konsep dan prinsip transaksi Islam, namun perbedaannya adalah penelitian ini menjelaskan secara lengkap prinsip transaksi Islam dan mencontohkan penerapan transaksi Islam dalam kegiatan ekonomi.